2018
DOI: 10.15253/2175-6783.2017000600017
|View full text |Cite
|
Sign up to set email alerts
|

Sexual partnerships of people living with the Human Immunodeficiency Virus

Abstract: Objective: to characterize the sexual partnerships established by people living with the Human Immunodeficiency Virus. Methods: an epidemiological study carried out with 173 participants in a medical assistance service specialized in the treatment of people with Human Immunodeficiency Virus. Data were collected through an individual interview with a specific questionnaire for the study. Pearson's Chi-square test was used to analyze the data. Results: the majority of the participants were male, young adults (54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
2
0
3
Order By: Relevance
“…Regarding the notifications related to race / color, it was observed a greater predominance in brown people, authors point out that the predominance of brown color in Brazil is characteristic because the color is self-declared and in the northeast there is a predominance of this ethnicity over all others, mainly due to the strong miscegenation. 14 A study conducted in Maranhão corroborates the data of this research, since it showed that 56.1% of the people affected were brown. The predominance of AIDS cases in the brown population is due to the fact that the Piaui population is mainly composed of self-declared brown people.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding the notifications related to race / color, it was observed a greater predominance in brown people, authors point out that the predominance of brown color in Brazil is characteristic because the color is self-declared and in the northeast there is a predominance of this ethnicity over all others, mainly due to the strong miscegenation. 14 A study conducted in Maranhão corroborates the data of this research, since it showed that 56.1% of the people affected were brown. The predominance of AIDS cases in the brown population is due to the fact that the Piaui population is mainly composed of self-declared brown people.…”
Section: Discussionsupporting
confidence: 82%
“…[12][13] Although the outlook for this infection has changed over the years with the emergence of new medications, increased patient life expectancy and improved quality of life, HIV / AIDS-related problems are still a serious problem to public health, and the consequences of this reality are the number of people who get the syndrome despite the various intervention options. 14 The diverse treatment possibilities provide new perspectives for people living with HIV / AIDS, patients with undetectable viral load and adherence to treatment have an extremely low possibility of HIV virus transmission with over 90% reduction, In addition to providing positive health repercussions, people still have the possibility to rebuild their life projects, have a sexual partner and perform reproductive planning. 15 On the other hand, what is observed is a resurgence of this infection and the development of AIDS at a time when scientific advances in relation to this infection present promising possibilities to mitigate this impasse, the development of the syndrome among people living with HIV should be a rare possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants were heterosexual and homosexual, and among those who had a steady partner, a portion was serodiscordant. Research has shown that among PLHIV with a fixed partnership, seroconcordant companions are more common than serodiscordant (36) , and when the partner's serology is unknown the HIV transmission may be greater compared to the situation in which the partner's seropositivity is known (37) .…”
Section: Discussionmentioning
confidence: 99%
“…Todo este contexto promueve la aparición de relaciones matrimoniales entre personas con VIH en las que los dos están infectados por el virus, llamados seroconcordantes, o en las que solo uno de ellos está infectado, es decir, parejas serodiferentes. A pesar del cambio en el enfrentamiento de la infección por VIH/SIDA, que pasó de ser una enfermedad letal a tener una cronicidad controlada que no tiene cura, pero tiene tratamiento, esta situación todavía representa un gran reto para los profesionales de la salud, con respecto a medidas de prevención y el nivel de información que abarca este problema (3,4) .…”
Section: Introductionunclassified
“…Las parejas sexuales infectadas enfrentan problemas que van desde el riesgo de transmisión del VIH, a través de las relaciones sexuales, el estigma e incluso la gestión de la diferencia serológica, con respecto a la decisión reproductiva (3) .…”
Section: Introductionunclassified